Plectin-1 as a Biomarker of Malignant Progression in Intraductal Papillary Mucinous Neoplasms: A Multicenter Study. Issue 9 (October 2016) - Moris, Maria; Dawson, David W.; Jiang, Jennifer; Lewis, Jason; Nassar, Aziza; Takeuchi, Kenneth K.; Lay, Anna R.; Zhai, Qihui; Donahue, Timothy R.; Kelly, Kimberly A.; Crawford, Howard C.; Wallace, Michael
Abstract : Objective: This study aimed to evaluate Plectin-1 expression as a biomarker of malignant risk for intraductal papillary mucinous neoplasms (IPMNs). Methods: Plectin-1 immunohistochemistry (IHC) was performed retrospectively on surgical (n = 71) and cytological (n = 33) specimens from Mayo Clinic Jacksonville and UCLA Medical Center, including IPMNs with low-grade dysplasia, high-grade dysplasia (HGD), or an associated invasive adenocarcinoma. Results: Plectin-1 expression was increased in invasive adenocarcinoma compared with adjacent in situ IPMN ( P = 0.005), as well as the in situ HGD component of IPMNs with invasive cancer compared with HGD of IPMNs without invasive cancer ( P = 0.02). Plectin IHC discriminated IPMNs with invasive adenocarcinoma from noninvasive IPMN (area under the curve [AUC] of 0.79, 75% sensitivity, and 85% specificity) but was insufficient for discriminating HGD IPMN from low-grade dysplasia IPMNs in surgical resections (AUC of 0.67, 56% sensitivity, and 64% specificity) or fine-needle aspiration specimens (AUC of 0.45). Conclusions: Although Plectin-1 IHC has insufficient accuracy to be used as a definitive biomarker for malignant risk in the evaluation of IPMN biopsy or cytological specimens, increased Plectin-1 expression observed in both invasive cancer and in situ HGD of malignant IPMNs suggests that it might be successfully leveraged as a cyst fluid biomarker or molecular imaging target. Abstract : Supplemental digital content is available in the text.